The revival of a so-called rotten fish: the ontogeny of the Devonian acanthodian Triazeugacanthus - Chevrinais, Marion (Biol Lett, 2015)
Since its original description as a chordate, the Late Devonian Scaumenella mesacanthi has been interpreted alternately as a prochordate, a larval ostracoderm and an immature acanthodian. For the past 30 years, these minute specimens were generally considered as decayed acanthodians, most of them belonging to Triazeugacanthus affinis. Among the abundant material of ‘Scaumenella’, we identified a size series of 188 specimens of Triazeugacanthus based on otolith characteristics. Despite taphonomic alteration, we describe proportional growth and progressive appearance of skeletal elements through size increase. Three ontogenetic stages are identified based on squamation extent, ossification completion and allometric growth. We demonstrate that what has been interpreted previously as various degrees of decomposition corresponds to ontogenetic changes.